PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) TERHADAP HASIL BELAJAR SISWA DENGAN VARIABEL MODERATOR KECERDASAN EKOLOGIS - Nurohmah Darmayanti; Rani Tania Pratiwi (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: The problem in this research is the low student learning outcomes. This is indicated bythe number of students who still get scores below the Minimum Completion Criteria. The lowlearning outcomes can be influenced by vaious factors one of which is the level of intelligencepossessed by the students themselves one of which is ecological intelligence.The purpose of thisresearch was to find the influence of the Project Based Learning model on learning outcomes withmoderators of ecological intelligence. The design in this research is to use a 2x2 factorial design.Based on the results of the analysis, the following results are obtained. First, there are differencesin student learning outcomes between classes using the Project Based Learning learning modeland classes that use the lecture learning model based on the significance values obtained by thelearning model that is equal to 0.003 0.05. Second, there is no difference in learning outcomesbetween students who have high ecological intelligence and students who have low ecologicalintelligence based on the obtained significance values of 0.925 0.05. Third, there is no interactionbetween the learning model and the ecological intelligence of the students in influencing thelearning outcomes based on the significance values obtained which is equal to 0.802 0.05. Thesuggestions in this research are that there is a need to prepare for project-based learning so thatstudents have no difficulty in solving problems and finding solutions in the form of works. Inproject-based learning the teacher acts as a facilitator and motivator so that material mastery andgood classroom management are needed.Keywords: Project Based Learning, Ecological Intelligence, Student Learning Outcomes.